Liquid chromatography–tandem mass/mass spectrometry method for the quantification of rabeprazole in human plasma and application to a pharmacokinetic study - Yu, Liyan; Deng, Haishan; Xiang, Bingren (Arzneimittelforschung, 2010)
A rapid, simple and sensitive reversedphase high-performance liquid chromatographic-tandem mass/mass spectrometry (HPLC/MS/MS) method has been developed for the measurement of rabeprazole (CAS 117976-89-3) concentrations in human plasma and its use in bioavailability studies has been evaluated. The method was linear in the concentration range of 0.05 −2.5 μg/ml. The lower limit of quantification (LLOQ) was 0.05 μg/ml in 1ml plasma sample. The intra- and inter-day relative standard deviation across three validation runs over the entire concentration range was less than 8.2% and 7.53%, respectively. This method was successfully applied for the evaluation of pharmacokinetic profiles of rabeprazole tablet in 18 healthy volunteers. The main pharmacokinetic parameters obtained were: AUC0–t 1415.88 ± 505.46 and 1457.44 ± 524.40 ng · h/ml, AUC0–∞ 1439.10 ± 507.47 and 1479.81 ± 527.83 ng h/ml, Cmax 678.24 ± 278.93 and 657.83 ± 250.86 ng/ml, t1/2 1.48 ± 0.19 and 1.38 ± 0.24 h, tmax 3.8 ± 0.8 and 3.7 ± 0.5 h for the test and reference formulations, respectively. No statistical differences were observed for Cmax and the area under the plasma concentration time curve for rabeprazole. 90% confidence limits calculated for Cmax and AUC from zero to infinity (AUC0–∞) of rabeprazole were included in the bioequivalence range (0.8–1.25 for AUC).
Keywords: CAS 117976-89-3; HPLC/MS/MS; Proton-pump inhibitors; Rabeprazole, biological availability, pharmacokinetics